Competition for migrants in a federation: Tax or transfer competition? - Marko Köthenbürger (Center for Economic Studies and ifo Institute (CESifo), 2012)
The paper provides an equilibrium analysis of how countries compete for migrants. The type of competition (tax or transfer competition) depends on whether the competing countries have similar policy preferences. With symmetric preferences, countries compete in taxes for migrants. With asymmetric preferences, migration competition takes place in income support levels. The results are robust to the degree of mobility and to whether high-income or low-income households are mobile. The results are relevant, e.g., for federal policies that tackle inefficient migration competition and for evaluating whether a country may wish to adopt unilateral migration-purchase policies.
Keywords: H70; J20; F20; 330; migration; redistribution; income taxation; government strategy; endogenous type of competition; Internationale Wanderung; Standortwettbewerb; Steuerwettbewerb; Sozialtransfer; Föderation; Theorie; EU-Staaten